2011
DOI: 10.1111/j.1476-5381.2011.01280.x
|View full text |Cite
|
Sign up to set email alerts
|

The dual neuroprotective–neurotoxic profile of cannabinoid drugs

Abstract: Extensive in vitro and in vivo studies have shown that cannabinoid drugs have neuroprotective properties and suggested that the endocannabinoid system may be involved in endogenous neuroprotective mechanisms. On the other hand, neurotoxic effects of cannabinoids in vitro and in vivo were also described. Several possible explanations for these dual, opposite effects of cannabinoids on cellular fate were suggested, and it is conceivable that various factors may determine the final outcome of the cannabinoid effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 137 publications
3
36
0
3
Order By: Relevance
“…The hypoxic-ischemic insult in our model produces more severe multiorgan damage compared to these studies [2,3,4,5]. As the effects of cannabinoids have been shown to depend both on the dose and pathophysiological setting [11,12], we hypothesized that higher doses of CBD could be required to demonstrate efficacy in this animal model.…”
Section: Introductionmentioning
confidence: 77%
“…The hypoxic-ischemic insult in our model produces more severe multiorgan damage compared to these studies [2,3,4,5]. As the effects of cannabinoids have been shown to depend both on the dose and pathophysiological setting [11,12], we hypothesized that higher doses of CBD could be required to demonstrate efficacy in this animal model.…”
Section: Introductionmentioning
confidence: 77%
“…Previous animal studies have already demonstrated hepatoprotective effects of various cannabinoid drugs [6,7,8,9,10,11,12,25,26]. It should be noted, however, that these studies presented a common experimental features: the doses that were administrated intraperitonealy ranged between 3 and 20 mg/kg (the doses that also induce the conventional acute effects of cannabinoids).…”
Section: Discussionmentioning
confidence: 92%
“…Oxidative stress and inflammatory stimuli may trigger hepatic endocannabinoid production [6]. The protective effect of various cannabinoid agonists has previously been demonstrated in a well characterized mouse model of hepatic I/R injury [6,7,8,9,10,11,12]. All these cannabinoids has been applied at high doses (3-20 mg/kg) that also induce the conventional pharmacological effects of cannabinoids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as no healthy cannabis users were included as a control group, it remains unclear whether this effect of cannabis was specific for schizophrenic patients. Interestingly, several studies in experimental animals showed that cannabinoids may have opposing effects depending on whether the animals were concomitantly treated with neurotoxic agents, i.e., cannabinoids were toxic when given alone, but neuroprotective when given in combination with other neurotoxic agents [77][78][79][80]. Taken together, there is some evidence to suggest that cannabinoids may have negative effects on certain neuropsychological functions, but may also be associated with beneficial effects in cases where (specific) brain dysfunctions already exist.…”
Section: Discussionmentioning
confidence: 94%